Football fan engagement: sponsorship brand value and consumer purchase intentions - Varea-Calero, Alfredo David; Ramírez-Hurtado, José M.; Rejón-Guardia, Francisco; Berbel-Pineda, Juan M (Emerald, 2025)
Purpose This study aims to analyse the influence of football fans' involvement on sponsor brand equity and their purchase intention toward the sponsoring brand. To achieve this, we specified a structural model examining the relationships between engagement, brand equity and fans’ purchase intentions. Design/methodology/approach The data for this study were collected using a structured questionnaire. Three football teams from the city of Quito (Ecuador) that compete in the first division of Ecuadorian professional football were considered. For data collection, both personal interviews and a web link were used. The personal interviews were carried out directly with the fans of the three teams in the vicinity of the stadiums, prior to matches of the Ecuadorian League. Findings The study concluded that a greater involvement of fans with a football club positively influences both the valuation of the sponsoring brand and the intention to purchase the product and/or service of the sponsoring brand. Practical implications This work contributes to the literature on brand equity. On the one hand, from the companies’ perspective, it is important for brand managers to realise that football fans constitute an especially significant section of the public to strengthen the brand and even to buy the products of the sponsoring brand. On the other hand, from the point of view of the clubs, it should be borne in mind that the involvement of the fans with the clubs constitutes a major factor in strengthening the sponsoring brands. Originality/value Most of the research in the literature has studied purchase intention towards the club brand but not towards the sponsoring brand. The research, which is applied to the football industry, conceptually extends the customer-based brand equity (CBBE) model by including the perspective of football fans’ involvement with their clubs.
https://openpolicyfinder.jisc.ac.uk/id/publication/2949
Keywords: Fútbol - Aspectos económicos; Patrocinio; Gestión de producto; Brand value; Football; Fan involvement; Purchase intention; Sponsorship